Biosafety in Dental Health Care During the COVID-19 Pandemic: A Longitudinal Study - Miguita, Lucyene; Martins-Chaves, Roberta Rayra; Geddes, Victor Emmanuel Viana; Mendes, Suellen da Rocha; Costa, Sara Ferreira dos Santos; Fonseca, Paula Luize Camargos; Menezes, Diego; Souza, Rafael Marques de; Queiroz, Daniel Costa; Alves, Hugo José; Freitas, Raphaela Alvarenga Braga de; Cruz, Aline Fernanda; et al. (Frontiers in Oral Health, 2022)
Background: The COVID-19 pandemic had quite an impact on dental health care. Concerns about the risk of SARS-CoV-2 transmission by contaminant fluids, droplets formation during several dental procedures, highly impacted on dental health care, drastically reducing the number of dental procedures worldwide. To monitor contamination of SARS-CoV-2 in dental clinics during activities return of students at university, a longitudinal study was carried out. Methods: SARS-CoV-2 RNA was screened in a dental school clinic environment and personnel (professors, undergraduate dental students, dental assistants, and patients) from January 11th to March 12th, 2021 (9 weeks). Serological testing was performed on dental health care professionals (DHCP) in two-time points. Additionally, samples with low Ct were sequenced to identify the circulating SARS-CoV-2 variant and possible transmission clusters. Results: We found a low number of dental staff (5.8%), patients (0.9%), and environment sites (0.8%) positive for SARS-CoV-2. Most positive cases were asymptomatic to mild symptoms, and two asymptomatic DHCP presented prolonged infection. 16.2% of DHCP showed IgM or IgG antibodies against SARS-CoV-2 in the 1st week showing previous exposure to COVID-19, and 1/3 of them had undetected antibodies in the last weeks. The variant zeta (P.2) could be detected. No cross-infection was observed between participants. Conclusion: Our study suggests that dental practice can be executed safely when control measures and biosafety protocols are applied adequately. DHCP and patient testing, patient telemonitoring, proper use of personal protection equipment, and surfaces sanitization are essential to avoid SARS-CoV-2 cross-infection in dental practice.